1999
DOI: 10.1046/j.1365-2990.1999.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for astrogliosis in brains of schizophrenic patients. A post‐mortem study

Abstract: Schizophrenia is clinically and neuropsychologically characterized by severe cognitive and functional impairment suggesting the presence of a neurodegenerative process in the brains of affected individuals. A variety of neuroanatomical changes have been described such as loss and disorientation of neurons in grey and white matter and cortical atrophy. However, the neuropathological basis for schizophrenia is still unclear. In the present study we monitored the density of GFAP-positive astrocytes in brains of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 32 publications
2
37
0
6
Order By: Relevance
“…Our Wndings conWrm animal studies showing increased mean astrocyte numbers in brains of aged mice [50], and the well-known lack of astrocytosis in schizophrenia [17,24]. Thus, the increasing number of astrocytes in the ageing brain shown in our study might serve as internal validity control for the results from the stereologic investigations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our Wndings conWrm animal studies showing increased mean astrocyte numbers in brains of aged mice [50], and the well-known lack of astrocytosis in schizophrenia [17,24]. Thus, the increasing number of astrocytes in the ageing brain shown in our study might serve as internal validity control for the results from the stereologic investigations.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, there are Wndings of both smaller [7,83] or unchanged [35] pyramidal neuron volumes in schizophrenia. Although some authors have noted a reduction of glial cells in the hippocampus of male patients with schizophrenia [23], astrogliosis has not been detected in the hippocampus of postmortem brains from patients with schizophrenia [17,24,65]. However, two-dimensional cell counting in only a few sections without considering the volume of the region carries methodological limitations through the inXuence of volume diVerences (e.g., mediated by neuropil degeneration) and tissue shrinkage by Wxation procedures.…”
Section: Introductionmentioning
confidence: 99%
“…37 Studies dealing with postmortem brains of schizophrenic individuals generally discount the role of gliosis in the etiology of this disorder. 10,[38][39][40] However, in at least one group of schizophrenic patients, increased GFAP and gliosis has been reported. 11 Moreover Stevens et al 41 and Bruton et al 12 have reported on periventricular gliosis especially in diencephalon of schizophrenics which is reminiscent of the increased GFAP-IR in the prenatally infected mouse brains, localized in proximity to cerebral cortical periventricular space and hippocampal fissure (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The neurodevelopmental theory is based on several abnormal findings in patients with schizophrenia: abnormal architectural arrangements of individual nerve cells, cell clusters, or cortical layers (Bogerts, 1993), neurons that are misplaced, mis-sized, and disorganized (Harrison, 1997), absence of normal cerebral structural asymmetry (Crow et al, 1989), relative stability of cognitive dysfunction (Rund, 1998), absence of gliosis (Falkai et al, 1999), and premorbid behavioral abnormalities (Jones et al, 1994). All these observations are consistent with a disorder of prenatal brain development, and argue against the notion that schizophrenia is a progressive degenerative brain disorder (Bogerts, 1993;Mjellem and Kringlen, 2001;Weinberger, 1995;Harrison, 1995Harrison, , 1997.…”
Section: Introductionmentioning
confidence: 99%